Metformin acts as a dual glucose regulator in mouse brain - Jin, Bo-Yeong; Kim, Hyun-Ju; Oh, Mi-Jeong; Ha, Na-Hee; Jeong, Yong Taek; Choi, Sang-Hyun; Lee, Jun-Seok; Kim, Nam Hoon; Kim, Dong-Hoon (Frontiers in Pharmacology, 2023)
Aims: Metformin improves glucose regulation through various mechanisms in the periphery. Our previous study revealed that oral intake of metformin activates several brain regions, including the hypothalamus, and directly activates hypothalamic S6 kinase in mice. In this study, we aimed to identify the direct effects of metformin on glucose regulation in the brain. Materials and Methods: We investigated the role of metformin in peripheral glucose regulation by directly administering metformin intracerebroventricularly in mice. The effect of centrally administered metformin (central metformin) on peripheral glucose regulation was evaluated by oral or intraperitoneal glucose, insulin, and pyruvate tolerance tests. Hepatic gluconeogenesis and gastric emptying were assessed to elucidate the underlying mechanisms. Liver-specific and systemic sympathetic denervation were performed. Results: Central metformin improved the glycemic response to oral glucose load in mice compared to that in the control group, and worsened the response to intraperitoneal glucose load, indicating its dual role in peripheral glucose regulation. It lowered the ability of insulin to decrease serum glucose levels and worsened the glycemic response to pyruvate load relative to the control group. Furthermore, it increased the expression of hepatic G6pc and decreased the phosphorylation of STAT3, suggesting that central metformin increased hepatic glucose production. The effect was mediated by sympathetic nervous system activation. In contrast, it induced a significant delay in gastric emptying in mice, suggesting its potent role in suppressing intestinal glucose absorption. Conclusions: Central metformin improves glucose tolerance by delaying gastric emptying through the brain-gut axis, but at the same time worsens it by increasing hepatic glucose production via the brain-liver axis. However, with its ordinary intake, central metformin may effectively enhance its glucose-lowering effect through the brain-gut axis, which could surpass its effect on glucose regulation via the brain-liver axis.